Kepastian Hukum Undang-Undang Cipta Kerja Bidang Kesehatan Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Weppy Susetiyo; Muhammad Zainul Ichwan; Anik Iftitah; Tasya Imelda Dievar (Universitas Islam Balitar, Blitar, 2022)
The enactment of the extraordinary job creation law changes the legislation in the health sector. However, the status of the Job Creation Law became unconstitutional or conditionally unconstitutional after the decision of the Constitutional Court 91/PUU-XVIII/2020 which granted part of the formal review of the Job Creation Law. Through normative legal research, research is produced that; even though Law 13/2022 has been promulgated on the Formation of Legislation which accommodates the preparation of laws and regulations using the omnibus law method; implementation of the law on: simplification of the articles in the Health Law and Hospital Law, medical health services that are not subject to VAT, providing medical health services not only for health workers and assistants for health workers, and implementing hospital accreditation every three years; remain valid and for two (2) years there may be no other related (new) regulations, for the sake of realizing benefits, certainty, justice, and the greater interest of many.